Multi-Functional Drug Carrier Micelles With Anti-inflammatory Drug - Wang, Wei-Jie; Huang, Yin-Chou; Su, Chao-Ming; Ger, Tzong-Rong (Frontiers in Chemistry, 2019)
The multi-functional micelles poly(N-isopropylacrylamide-co-N,N-dimethylacrylamide-co-10 undecanoic acid)/CM-Dextran Fe3O4 (PNDU/CM-Dex Fe3O4) were poly (NIPAAm-co-DMAAm-co-UA) (PNDU) grafting hydrophilic CM-Dextran Fe3O4 which possess pH-dependent temperature response and magnetic response. In this research, anti-inflammation drug Hesperetin was encapsulated by micelles using membrane dialysis method to obtain the different ratio of Hesperetin-embedded P5DF10, P10DF10, and P20DF10. These micelles were characterized by Fourier transform infrared spectroscopy, 1H-NMR, thermogravimetric analyzer, and superconducting quantum interference device magnetometer. The morphology and particle size of micelles was observed by transmission electron microscopy and dynamic light scattering. The low critical solution temperature of the P10DF10 micelles is in pH 6.6 at about 37.76 °C and in pH 7.4 at about 41.70 °C. The biocompatibility of micelles was confirmed by cytotoxicity study. Inflammatory inhibition of hesperetin-embedded P10DF10 micelles also studied through RAW264.7. Hesperetin-embed P10DF10 micelles suppressed LPS-induced inflammatory response. Via immunofluorescence cell staining demonstrate that Hesperetin-embed P10DF10 micelles inhibited the activation of NF-κB p60 and markedly attenuated in a drug dose-dependent manner. At a concentration of 1000 ug/ml, an inflammatory rate can be reduced to 36.9%. Based on these results, the hesperetin-embed P10DF10 micelles had successfully synthesized and enable to carry and release the anti-inflammatory drugs, which instrumental for biomedical therapy and applications.